The diffident naturalist : Robert Boyle and the philosophy of experiment - Sargent, Rose-Mary (Science and its conceptual foundations., 1995)
In a provocative reassessment of one of the quintessential figures of early modern science, Rose-Mary Sargent explores Robert Boyle's philosophy of experiment, a central aspect of his life and work that became a model for mid- to late seventeenth-century natural philosophers and for many who followed them. Sargent examines the philosophical, legal, experimental, and religious traditions--among them English common law, alchemy, medicine, and Christianity--that played a part in shaping Boyle's experimental thought and practice. The roots of his philosophy in his early life and education, in his re.